Thickness dependences of optical constants for thin layers of some metals and semiconductors - Kovalenko, S.A.; Lisitsa, M.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
The review comprises investigations devoted to determination of refractive index and absorption coefficient dependences on thickness for thin films of metals and atomic semiconductors. It has been shown that erroneous results were obtained in many papers and correct interpretation of the latter is absent. The reason that braked the solution of the problem of dimensional optical phenomena in thin layer physics was ascertained.